Salman Al-Farisi dan bangsa parsi dari perspektif pemikiran Islam: analisis dari aspek modal insan - Wan Ali, Wan Zailan Kamaruddin; Ismail, Ahmad Zuhdi (Lembaga Penelitian dan Pengembangan, Pusat Penelitian Kerukunan Umat Beragama, UIN Sultan Syarif Kasim Riau, 2009)
This article as the title indicates is to examine the life and background of Salman al-Farisi and his position in Islam and especially in the world of Persian people within the Islamic Thought. The discussion will also be focusing on the nation of Salman al-Farisi and their contribution to Islam and the world.